Analytical Model of Cage Induction Machine Dedicated to the Study of the Inner Race Bearing Fault - Marouane Hadjami; Hubert Razik; Mohamed El Kamel Oumaamar; Abdelmamek Kezzar (Institute of Advanced Engineering and Science, 2018)
This paper presents a new analytical model for inner bearing raceway defect. The model is based on the presentation of different machine inductances as Fourier series without any kind of reference frame transformation. The proposed approach shows that this model is able to give important features on the state of the motor. Simulation based on spectral analysis of stator current signal using Fast Fourier Transform (FFT) and experimental results are given to shed light on the usefulness of the proposed model.